2008
DOI: 10.1097/brs.0b013e318166e0a2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relative Needle Diameter in Puncture and Sham Injection Animal Models of Degeneration

Abstract: A needle puncture may directly alter mechanical properties via nucleus pulposus depressurization and/or anulus fibrosus damage, depending on the relative needle size. As more basic science research is aimed at treating disc degeneration via injection of therapeutic factors, these findings provide guidance in design of animal studies. Such studies should consider the relative needle size and include sham control groups to account for the potential effects of the needle injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
212
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(234 citation statements)
references
References 53 publications
12
212
1
2
Order By: Relevance
“…[36][37][38] Establishing a relationship between disc behavior and external osmotic pressure will be helpful for measuring intradiscal pressure without the use of pressure sensors, which might alter disc mechanics because of annular injuries. 39 The bovine caudal disc is an ideal animal model to study disc mechanics of the healthy human disc, based on similarities in biomechanical composition, disc height, swelling pressure, and mechanical properties. [30][31][32][33]40 However, the bovine discs do not exhibit signs of degeneration or aging like the human disc.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Establishing a relationship between disc behavior and external osmotic pressure will be helpful for measuring intradiscal pressure without the use of pressure sensors, which might alter disc mechanics because of annular injuries. 39 The bovine caudal disc is an ideal animal model to study disc mechanics of the healthy human disc, based on similarities in biomechanical composition, disc height, swelling pressure, and mechanical properties. [30][31][32][33]40 However, the bovine discs do not exhibit signs of degeneration or aging like the human disc.…”
Section: Discussionmentioning
confidence: 99%
“…This information would give an indication of whether the cells were alive and functioning and whether they were producing appropriate matrix macromolecules to restore disc height and biomechanical behaviour. Cartilage repair has been assessed through biopsies but since even needle puncture, depending on its size, can lead to disc degeneration [25,54] biopsies are unlikely to be used to assess disc repair clinically.…”
Section: How Do We Assess Success?mentioning
confidence: 99%
“…Elliot et al 11 suggested that needle puncture inducing discal changes is dependent on the ratio of needle diameter to the disc height. In this case, disc changes were universal for the ratio over 40%.…”
Section: Discussionmentioning
confidence: 99%